HUBUNGAN MANAJEMEN DIRI DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 3 WATAMPONE KABUPATEN BONE - SUGIAN NURWIJAYA (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This research is an ex-post facto study that is correlational in nature to find a causal relationship between self-management and mathematics learning achievement of eighth grade students in SMP Negeri 3 Watampone, Bone Regency. The hypothesis of this study is that there is a positive relationship between self-management and mathematics learning achievement of eighth grade students of SMP Negeri 3 Watampone. The population of this study was the eighth grade students of SMP Negeri 3 Watampone Bone Regency and the sample in this study was 122 students.The data collection technique carried out in this study was derived from self-management questionnaires distributed to 122 respondents and report card grades in mathematics subjects of SMP Negeri 3 Watampone. The results of this study reveals that the average self-management score of students is 3.67 which is in the high category with an interval of 3.4 ?X 4.2. While the average value of student learning achievement is 80 which is in the good category with an interval score of 61 - 80. From the results of hypothesis testing shows that the correlations obtained a significant value of 0,000 (0,000? 0,05) which means self-management is positively related to achievement study mathematics class VIII SMP Negeri 3 Watampone, Bone Regency.